Effects of COX inhibition on experimental pain and hyperalgesia during and after remifentanil infusion in humans - Lenz, Harald; Raeder, Johan; Draegni, Tomas; Heyerdahl, Fridtjof; Schmelz, Martin; Stubhaug, Audun (Pain (Amsterdam), 2011)
Opioids may enhance pain sensitivity resulting in opioid-induced hyperalgesia (OIH). Activation of spinal cyclooxygenase may play a role in the development of OIH. The aim of this study was to demonstrate remifentanil-induced postinfusion hyperalgesia in an electrical pain and a cold pain model, and to investigate whether COX-2 (parecoxib) or COX-1 (ketorolac) inhibition could prevent hyperalgesia after remifentanil infusion. Sixteen healthy males were enrolled in this randomized, double-blind, placebo-controlled crossover study. Each subject went through 4 sessions: control, remifentanil, parecoxib + remifentanil, and ketorolac + remifentanil. Transcutaneous electrical stimulation induced acute pain and areas of pinprick hyperalgesia. The areas of pinprick hyperalgesia were assessed before, during, and after a 30-minute infusion of either remifentanil or saline. The cold-pressor test (CPT) was performed before, at the end of, and 1 hour after the infusions. The subjects received a bolus of either saline, 40 mg parecoxib, or 30 mg ketorolac intravenously after the first CPT. The areas of pinprick hyperalgesia and CPT pain after the end of remifentanil infusion increased significantly compared to control ( P < 0.001 and P = 0.005, respectively). Pretreatment with parecoxib or ketorolac reduced the postinfusion area of pinprick hyperalgesia ( P < 0.001 and P = 0.001, respectively), compared to the remifentanil group. Parecoxib reduced the area significantly more than ketorolac ( P = 0.009). In the CPT, pretreatment with parecoxib or ketorolac did not prevent postinfusion hyperalgesia. These results demonstrated OIH in both models, and may suggest that COX-2 inhibition is more important than COX-1 inhibition in reducing hyperalgesia. Remifentanil-induced hyperalgesia was demonstrated for both electrically induced pain and cold-pressor pain. Both parecoxib and ketorolac prevented hyperalgesia in the electrical model, parecoxib to a larger extent.